Real-time monitoring and just-in-time intervention for adherence to pre-exposure prophylaxis among men who have sex with men in China: a multicentre RCT study protocol - Xia Jin; Hongyi Wang; Hang Li; Zhenxing Chu; Jing Zhang; Qinghai Hu; Wei Lv; Xiaojie Huang; Yaokai Chen; Hui Wang; Xiaoqing He; Lukun Zhang; et al. (BMC, 2020)
Abstract Background Pre-exposure prophylaxis (PrEP) is an effective biomedical strategy to prevent transmission of HIV infection, although medication adherence remains a challenge. We present the protocol for a multicentre randomised controlled trial to measure the effectiveness of a real-time monitoring and just-in-time intervention on medication adherence among PrEP users in China. Methods Study participants will include 1000 men who have sex with men (MSM) from four cites in China (Shenyang, Beijing, Chongqing and Shenzhen) attending a tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) PrEP project as part of a real-world, prospective multicentre cohort study (CROPrEP). Participants will be randomised into the intervention and control arms in a 1:1 ratio. Participants in the intervention arm will be provided with remote real-time monitoring equipment that triggers twice just-in-time SMS (Short Messaging Service) medication reminders to PrEP users every half an hour when a scheduled dosage is missed, and followed with just-in-time SMS medication reminders to clinicians half an hour when there is no supplement after the second just-in-time SMS reminder to PrEP users. Clinicians will initiate individualised telephone intervention as soon as possible upon receipt of the just-in-time SMS missed dose alert. Those in the control arm will only receive generic weekly SMS reminders. The study will last 6 months. Participants will be seen at follow-up visits at three and 6 months. Trial outcomes to be measured include self-reported adherence assessed via questionnaire and pill counts, as well as drug concentration test results. Discussion Medication adherence is critical to achieve optimal benefits from PrEP. This study will be the first individualised behaviour intervention using real-time technology to increase adherence among MSM PrEP users globally. If found effective, a real-time monitoring and just-in-time intervention system may be utilized for improving adherence and thus effectiveness of global PrEP application. Trial registration This study registered at ClinicalTrials.gov ( ChiCTR1900025604 ) on September 2, 2019.